Alternatives to Metamaterial Based Antennas for Gain and Bandwidth Enhancement. Issue 4 (19th May 2023) - Nimbolkar, Ankit; Kumar, Hemant; Kumar, Girish
Abstract : Several metamaterial antenna configurations have been proposed in the literature for gain and bandwidth enhancement. However, these antennas are rarely used in commercial applications due to complexity in their design and fabrication process. In this paper, different configurations of electromagnetically coupled microstrip antennas and arrays are proposed as an alternative antenna design for gain and bandwidth enhancement. A comparison is made between the configurations proposed in this paper and the metamaterial configurations reported in the literature. The proposed configurations have better gain and bandwidth than the metamaterial configurations within the smaller volume.